Pakistan’s Economic Development and the Influence of Green Fiscal Policies on the Country’s Economy - Marwa Batool; Fatima Zahra; Asif Z. Warsi; Muhammad Adil; Hafiz Muhammad Sarmad Abid; Muhammad Alfahad (Dialogue Social Science Review (DSSR), 2025)
The trend of green fiscal policies is increasing in many developing countries in the contemporary world. This paper tends to investigate the impression of green fiscal policies on financial development in Pakistan. In this accordance, this study investigates the impact of two significant features of green fiscal policies known as investment in renewable energy resources (IRE) and green innovation (GI) on economic performance (EP). In addition to it, the mediating impact of environmental attitude (EA) has also been examined on the association of IRE and EP and GI and EP. To efficiently reach a reliable conclusion, the quantitative method has been utilized in this paper on the basis of which a survey has been taken from economic experts in Pakistan. According to the results, IRE and GI significantly affect Pakistan's GDP growth. The statistical evaluation was carried out by means of SPSS. It is vital to note that EA plays a substantial role in mediating the connection between IRE and EP, its impact on GI and EP is minimal. The respective findings imply that in terms of green fiscal policies IRE and GI can be promoted with positive EA as these determinants have extensive potential to improve economic growth in Pakistan. The consequences of this research offer important insinuations for practitioners of economic institutes, policy-makers, and research scholars.